2009
DOI: 10.1017/s0266467409006129
|View full text |Cite
|
Sign up to set email alerts
|

Development of allometric relationships for accurate estimation of above- and below-ground biomass in tropical secondary forests in Sarawak, Malaysia

Abstract: Abstract:We developed allometric relationships between tree size parameters (stem diameter at breast height (dbh), at ground surface (D0) and tree height) and leaf, stem, small-root (diameter <5 mm) and total root biomass in various tropical secondary-forest trees in Sarawak, Malaysia. In total, 136 individuals from 23 species were harvested to measure above-ground parts. Root systems of 77 individuals of 16 species were also excavated. The coefficients of correlation for the obtained allometric relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 54 publications
8
84
4
1
Order By: Relevance
“…In addition, patches with AGB exceeding 200 Mg ha -1 were classified as intact forest; this threshold is widely used to differentiate intact and degraded tropical forests (Asner 2002, Morel et al 2012. We used allometric equations developed specifically for Bornean rainforest trees (Yamakura et al 1986, Basuki et al 2009, Kenzo et al 2009). The AGB (kg) of trees in intact forests was calculated from DBH (cm) as follows (eqn.…”
Section: Field Data Collectionmentioning
confidence: 99%
“…In addition, patches with AGB exceeding 200 Mg ha -1 were classified as intact forest; this threshold is widely used to differentiate intact and degraded tropical forests (Asner 2002, Morel et al 2012. We used allometric equations developed specifically for Bornean rainforest trees (Yamakura et al 1986, Basuki et al 2009, Kenzo et al 2009). The AGB (kg) of trees in intact forests was calculated from DBH (cm) as follows (eqn.…”
Section: Field Data Collectionmentioning
confidence: 99%
“…Chave et al (2005) developed benchmark models for the tropics involving diameter, wood density, and height according to forest types. Although Chave's models perform reasonably well in certain sites in Southeast Asia (Rutishauser et al 2013) and Africa (Vieilledent et al 2012;Fayolle et al 2013), most of the other studies show higher uncertainty in biomass estimates compared to those developed locally (Basuki et al 2009;Kenzo et al 2009a;van Breugel et al 2011;Alvarez et al 2012;Goodman et al 2014). In another recent benchmark pantropical study, Feldpausch et al (2012) showed substantial variation in biomass distribution and forest structure among regions and continents and concluded that future biomass models based on continents and regions may prove more robust than pantropical models.…”
Section: Introductionmentioning
confidence: 93%
“…The belowground root productivity in this database is a combination of coarse (generally >2mm diameter) as well as fine root (generally <2mm diameter) data. Most estimates of coarse root biomass and productivity are a ratio developed from allometric relationships developed for a particular species (e.g., Kenzo et al 2009). However fine root NPP data were obtained from direct measures of fine root growth using a diversity of field sampling methods (e.g., root cores, in-growth cores, mini-rhizotrons, etc).…”
Section: Variable Key Groupsmentioning
confidence: 99%